ALAT TUKAR DI PAPUA DAN KOMODITASNYA - Tolla, Marlin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Exchange of goods that eventually led to trade in the coastal areas and central highlands of Papua occur because of increased demand for commodities. It is also caused by the influence of the contact that occurred between the inhabitants papua papua with residents from the outside. The exchange of goods conducted in Papua between the tribes who live in coastal regions and tribes in the mountainous areas in the beginning is made very simple without the use of a medium of exchange, ie, mutual exchange of goods with goods that are considered necessary by each party to the transaction in a place which been agreed. Then on the next period, then the familiar medium of exchange in transactions that ultimately the emergence of trade. This occurred after the entry of some of the influences brought by the party who began to explore commodities - commodities such as birds of paradise in Papua, masohi woods, slaves and other commodities. As for the goods as a means to exchange commodities mentioned above, among others: the goods are made from bronze, ceramic, metal, cloth of timor, and others. Along with the inclusion of these objects to the Papuans, the tribe - the tribal papua then started using some tools, which have value in their own trade, among others: stone axes, seashells, beads and others who until now is still used mainly in traditional ceremonies like marriage